Comparison and evaluation of aceclofenac nanoemulsion formulation using homogenization and ultrasonication techniques - Jahan Saiky, Kazi Mustari (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020